Improving the high-temperature oxidation resistance of TiB2 thin films by alloying with Al. (1st September 2020) - Bakhit, Babak; Palisaitis, Justinas; Thörnberg, Jimmy; Rosen, Johanna; Persson, Per O.Å.; Hultman, Lars; Petrov, Ivan; Greene, J.E.; Greczynski, Grzegorz
Abstract: Refractory transition-metal diborides (TMB2 ) are candidates for extreme environments due to melting points above 3000 °C, excellent hardness, good chemical stability, and thermal and electrical conductivity. However, they typically suffer from rapid high-temperature oxidation. Here, we study the effect of Al addition on the oxidation properties of sputter-deposited TiB2 -rich Ti1-x Alx By thin films and demonstrate that alloying the films with Al significantly increases the oxidation resistance with a slight decrease in hardness. TiB2.4 layers are deposited by dc magnetron sputtering (DCMS) from a TiB2 target, while Ti1-x Alx By alloy films are grown by hybrid high-power impulse and dc magnetron co-sputtering (Al-HiPIMS/TiB2 -DCMS). All as-deposited films exhibit columnar structure. The column boundaries of TiB2.4 are B-rich, while Ti0.68 Al0.32 B1.35 alloys have Ti-rich columns surrounded by a Ti1-x Alx By tissue phase which is predominantly Al rich. Air-annealing TiB2.4 at temperatures above 500 °C leads to the formation of oxide scales that do not contain B and mostly consist of a rutile-TiO2 ( s ) phase. The resulting oxidation products are highly porous due to the evaporation of B2 O3 ( g ) phase as well as the coarsening of TiO2 crystallites. This poor oxidation resistance is significantly improved by alloying with Al. While air-annealing at 800 °C for 0.5 h results in the formation of an 1900-nm oxide scale on TiB2.4, the thickness of the scale formed on the Ti0.68 Al0.32 B1.35 alloys is 470 nm. The enhanced oxidation resistance is attributed to the formation of a dense, protective Al-containing oxide scale that considerably decreases the oxygen diffusion rate by suppressing the oxide-crystallites coarsening. Graphical abstract: Image, graphical abstract